STRATEGI PENATAAN APARATUR DAERAH MELALUI PENDEKATAN “BEST PRACTICES” - A., Rustan (Pusjar SKPP Lembaga Administrasi Negara, 2010)
This article aims to know about the strategy of human resource structuring by adopting best practices approach from other regions. The strategy can also be expected to solve the problems in the field of employment. The analysis results mix- strategies with 6 (six) steps of structuring human resources. Through the implementation of these strategy, it is expected that the effectiveness, efficiency, and professionalism of apparatus can be achieved Keywords : Strategy, Human Resource, Best Practice